Impact of Early Conventional Treatment on Adult Bone and Joints in a Murine Model of X-Linked Hypophosphatemia - Cauliez, Axelle; Zhukouskaya, Volha V.; Hilliquin, Stéphane; Sadoine, Jérémy; Slimani, Lotfi; Miceli-Richard, Corinne; Briot, Karine; Linglart, Agnès; Chaussain, Catherine; Bardet, Claire (Frontiers in Cell and Developmental Biology, 2021)
X-linked hypophosphatemia (XLH) is the most common form of genetic rickets. Mainly diagnosed during childhood because of growth retardation and deformities of the lower limbs, the disease affects adults with early enthesopathies and joint structural damage that significantly alter patient quality of life. The conventional treatment, based on phosphorus supplementation and active vitamin D analogues, is commonly administered from early childhood to the end of growth; unfortunately, it does not allow complete recovery from skeletal damage. Despite adequate treatment during childhood, bone and joint complications occur in adults and become a dominant feature in the natural history of the disease. Our previous data showed that the Hyp mouse is a relevant model of XLH for studying early enthesophytes and joint structural damage. Here, we studied the effect of conventional treatment on the development of bone and joint alterations in this mouse model during growth and young adulthood. Mice were supplemented with oral phosphorus and calcitriol injections, following two timelines: i) from weaning to 3 months of age and ii) from 2 months to 3 months to evaluate the effects of treatment on the development of early enthesophytes and joint alterations, and on changes in bone and joint deformities already present, respectively. We showed that early conventional treatment improved bone microarchitecture, and partially prevented bone and joint complications, but with no noticeable improvement in enthesophytes. In contrast, later administration had limited efficacy in ameliorating bone and joint alterations. Despite the improvement in bone microarchitecture, the conventional treatment, early or late, had no effect on osteoid accumulation. Our data underline the usefulness of the Hyp murine model for preclinical studies on skeletal and extraskeletal lesions. Although the early conventional treatment is important for the improvement of bone microarchitecture, the persistence of osteomalacia implies seeking new therapeutic strategies, in particular anti-FGF23 approach, in order to optimize the treatment of XLH.